Context-dependent utility overrides absolute memory as a determinant of choice - Pompilio, L. (2010)
A core problem of decision theories is that although decisionmakers' preferences depend on learning, their choices could be driven either by learned representations of the physical properties of each alternative (for instance reward sizes) or of the benefit (utility and fitness) experienced from them. Physical properties are independent of the subject's state and context, but utility depends on both. We show that starlings' choices are better explained by memory for context-dependent utility than by representations of the alternatives' physical properties, even when the decisionmakers' state is controlled and they have accurate knowledge about the options' physical properties. Our results support the potential universality of utility-driven preference control.